Catch Composition and Financial Feasibility of Senangin Gill Net Fishing Gear at the Fisheries Port UPT in Riau Province - Hutabarat, Suryana Ardita; Zain, Jonny; Limbong, Irwan (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2025)
This study aims to analyze the catch composition and evaluate the financial feasibility of using senangin gill nets at the Fisheries Port Technical Implementation Unit (UPT) in Riau Province. Primary data were collected through direct observation and interviews with boat-owning fishermen, while secondary data were obtained from relevant institutions. The results indicated that senangin fish (Eleutheronema tetradactylum) was the main catch with the highest CPUE values during the 2020–2023 period. The by-catch included mullet (Mugil cephalus), pomfret (Pampus argenteus), and catfish (Arius thalassinus). The financial feasibility analysis showed that the fishing operation is viable, with a positive Net Present Value (NPV), an Internal Rate of Return (IRR) exceeding the discount rate, a Payback Period (PP) of less than five years, and a Benefit-Cost Ratio (BCR) greater than one. Therefore, the use of senangin nets is considered ecologically sustainable and economically beneficial for local fishermen.